Substantiation of environmental and resource-saving technologies for void filling under underground ore mining - Lyashenko, V.; Khomenko, O.; Golik, V.; Topolnij, F.; Helevera, O. (My University, 2020)
The object of research is the technology and technical means to clear the voids during the underground mining of ores in the disturbed arrays. One of the most problematic places is the filling of man-made voids that affect the occurrence and redistribution of the stress-strain state (SSS) of the rock mass. Their existence in the earth's crust provokes disturbance of the daily surface, as well as the influence of geomechanical and seismic phenomena, up to the level of earthquakes. Analytical researches, comparative analysis of theoretical and practical results by standard and new methods with the participation of the authors are performed. The peculiarities of the manifestation of mountain pressure in the rock massifs of a complex structure are considered, due to the intensity of the fracture structures (acoustic stiffness from 0.11 to 0.18 MPa/s, impact coefficient – 0.98). The conditions of manifestation of residual bearing capacity of disturbed rocks and translation of geomaterials into the volume compression mode were investigated (in the zone of disturbed rocks the attenuation coefficient decreases to 0.04–0.15 from the initial value of 0.25–0.35). The basic estimation of durability of workings and inhomogeneous rocks with a strength of 50–150 MPa at depths up to 600 m is shown, depending on the position of workings with respect to the elements of structural disturbance and the possibility of creating reliable structures. Conclusions have been made about the efficiency of the use of load-bearing structures from rocks of greater than 0.2 m in size and mechanical strength of more than 50 MPa, which allows to expose the roof without collapsing at spans of up to 50 m. the bearing layer of the rocks produced space can be filled by insulation or a hardener with a strength of up to 1.2 MPa. The research results can be used in the underground development of ore deposits of complex structure of Ukraine, the Russian Federation, the Republic of Kazakhstan and other developed mining countries of the world.
Keywords: mountain range; underground development; void filling; environmental and resource conservation technology; mining efficiency